ChemInform Abstract: 2‐Phenyl‐2‐(4‐phenyl‐1H‐1, 2, 3‐triazol‐1‐yl)ethanol as an Efficient and Versatile Auxiliary Ligand in Copper(II)‐Catalyzed Buchwald—Hartwig and Sharpless—Meldal C—N Bond‐Forming Reactions. Issue 35 (September 2015) - Sharghi, Hashem; Shiri, Pezhman
Abstract A variety of N‐aryl compounds and 1, 4‐disubstituted triazoles can be synthesized from the title reactions.